INFLUENCE OF UNIVERSITY CORPORATE CULTURE ON «ADORNATION» OF GRADUATES’ COMPETENCES - Maria A. Dremina; Galina A. Gorbunova; Vitaly A. Kopnov (Образование и наука)
The aim of the study is to identify the phenomenon and to describe the concept forming the competences of university graduates provided with signs of corporate identity.Methods. Methods of the system and comparative analysis, synthesis, generalisation, analogy are used in the presented paper.Results. The key role of corporate culture of high school in formation of actual competences providing future graduates success is proved on the basis of materials of the Russian and foreign researches. The social and pedagogical contradictions which are that the declared accounting of features of corporate culture in pedagogical process isn't provided with mechanisms of design of the competences provided with signs of corporate identity are revealed. Missions of modern leading high schools are analysed for the purpose of definition of these signs. The necessity of changing the model of corporate culture at the stage preceding the design of learning outcomes is justified.Scientific novelty. The concept of application of the model of HEI (Higher Education Institutions) corporate culture as a key reference point for forming competences provided with signs of corporate identity is offered. The concept considers features of transition of the Russian HEI to work in conditions fulfilling requirements of the Bologna agreement. The concept is caused also by an indicator «Success of university graduates, achievements of HEI in the process of selection of elite at national and international levels» by criterion «brand» in the model of National Universities Ranking. The new concept «adornation» (derived from a verb “to adorn”) in relation to process of forming the competences provided with signs of corporate identity is introduced. According to the offered concept, semantic filling of a mission and system of values allows adorning competences taking into account requirements of the social role of a graduate as a mission performer of HEI and helps the graduate in detail and in the best way to embody corporate valuable ideals in activity.Practical significance. The research results can be useful to teachers and managers of HEIs while monitoring systems of success of graduates.